The effect of an integrated education model on anxiety and uncertainty in patients undergoing cervical disc herniation surgery. Issue 133 (September 2016) - Chuang, Mei-Fang; Tung, Heng-Hsin; Clinciu, Daniel L.; Huang, Jing-Shan; Iqbal, Usman; Chang, Chih-Ju; Su, I.-Chang; Lai, Fu-Chih; Li, Yu-Chuan
Highlights: Reducing patients' anxiety and uncertainty are important issues in the practice of medicine. We developed a new method to educate patients in order to relieve patients' anxiety and uncertainty about upcoming surgeries. Our method consisting of integrating mobile devices, education platforms and three measurements (the State-Trait Anxiety Inventory (STAI), the Mishel Uncertainty in Illness Scale (MUIS), and a measure of satisfaction) were recorded pre and post-surgery. Both experimental and control groups showed a significant decrease in STAI and MUIS scores after surgery, but the experimental group exhibited a greater decrease in anxiety and uncertainty. Here we demonstrated that patients receiving newer education platform were more satisfied than those receiving conventional education or the currently available conventional education model. Abstract: Background: Educating patients about receiving surgical procedures is becoming an important issue, as it can reduce anxiety and uncertainty while helping to hasten decisions for undergoing time sensitive surgeries. We evaluated a new integrated education model for patients undergoing cervical disc herniation surgery using a quasi-experimental design. Methods: The participants were grouped into either the new integrated educational model ( n = 32) or the standard group ( n = 32) on the basis of their ward numbers assigned at admission. Anxiety, uncertainty, and patient satisfaction were measured before (pre-test) and after the educational intervention (post-test-1) and post-surgery (post-test-2) to assess the effectiveness of the model in this intervention. Results: We found that the generalized estimating equation modeling demonstrated this new integrated education model was more effective than the conventional model in reducing patients' anxiety and uncertainty ( p < 0.05). Patients were also more satisfied with our newly developed model as it takes a more holistic approach to individual health. Conclusion: This novel systemic educational model enhances patient's understanding of the medical condition and surgery while promoting patient–caregiver interaction for optimal patient health outcomes. We present a comprehensive and consistent platform for educational purposes in patients undergoing surgery as well as reducing the psychological burden from anxiety and uncertainty. Integrating medicine, nursing, and new technologies into an e-practice and e-learning platform offers the potential of easier understanding and usage. It could revolutionize patient education in the future.